DINAMIKA SISTEM KOTA-KOTA DAN PEMILIHAN ALTERNATIF PUSAT PERTUMBUHAN BARU DI KOTA SEMARANG - Reosa Andika Firmansyah; Hariyanto Hariyanto; Ariyani Indrayati (Geo-Image, 2017)
The dynamic development of Semarang was based on the development activity which brought the physical and social changes. The purposes of this research were to analyze the dynamics and variation of cities system development and the city character to choose or to determine the new alternative growth pole in Semarang, so that the area development distributed evenly. This research used descriptive analysis method with secondary data analysis. The areas of the research were 16 subdistricts in Semarang. The variables used were demografics and public facility. The former was used to analyze the hierarchy system and cities; while the latest was used to analyze the city character (city classes), to analyze the Spearman correlation and the making of area typology. In addition, the the program of Arc View was used to spatial analysis or mapping. The conclusion of this research was there was the primacy decreasing in Semarang followed by the increasing of the suburban area role which became the new growth pole. In addition, the researcher recommands the government to take political will policy in order to take some actions based on the research results by determining political document.